Soil phosphorus increases dry matter and nutrient accumulation and allocation in potato cultivars - Fernandes, Adalton Mazetti [UNESP]; Soratto, Rogério Peres [UNESP]; Pilon, Cristiane [UNESP] (Springer, 2015)
Understanding the influence of P in the pattern of production and partitioning of dry matter (DM) and nutrients to the tubers of potato cultivars is critical for development of rational fertilization strategies to optimize tuber yield. The objective of this study was to evaluate the effect of soil P availability (Low P: 10 mg dm(-3) and High P: 111 mg dm(-3)) in the leaf nutrients concentration, nutrients and DM accumulation and allocation to tubers of five potato cultivars (Agata, Asterix, Atlantic, Markies, and Mondial). The experiment was conducted under greenhouse conditions in pots containing 35 L of a Typic Acrortox soil. High P availability in the soil increased P concentrations in all plant organs, uptake of P and Cu, and DM production of all potato cultivars. The cultivars showed differences in the harvest index (HI) and uptake and allocation of N, K, Ca, Mg, S, Fe, Mn, and Zn to the tubers in response to P supply. Even with higher whole plant DM production and HI under high P availability in the soil, some of the cultivars did not increase the uptake and proportion allocated to the tubers of some nutrients as a response to the high P supply. This highly controlled greenhouse experiment was able to reveal cultivar differences in DM, HI, and nutrient accumulation influenced by P, a first step toward future studies exploiting these differences in the field production environment.
Keywords: Solanum tuberosum; Macronutrients; Micronutrients; Biomass partitioning; Nutrient partitioning